Karakteristik Butir Soal Dalam Evaluasi Pembelajaran Matematika (Studi Implementasi Praktikum Mahasiswa Jurusan Tadris Matematika di Tingkat MTs/SMP dan MA/SMA Se-NTB) - Erpin Evendi (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2018)
The purpose of this study is to find out; (1) Characteristics of items for semester exam math questions; (2) Whether or not there is a relationship between the number of items dropped based on the classical test theory using the ITEMAN program by using item analysis based on material, construction, and language in Mathematics. This research is a quantitative descriptive study with a survey approach, namely analyzing the characteristics of the items of the semester exam math questions, which meet the criteria of validity and reliability in theory, namely examining the questions empirically, using classical test theory. The conclusions in this study are; (1) Characteristics of semester exam questions in mathematics subjects, that there are categories accepted, less fulfilling, and many that do not meet, meaning that mathematics teachers must better understand the techniques of composing test instruments and non-tests, to support their skills in structuring questions qualitatively ; (2) There is a relationship between the number of mathematical questions that fall according to classical test theory and item analysis.